Distinctive Analysis of Land Cover Change Exposure of Karachi through Multi-Temporal Remotely Sensed Imageries - Abbasi, Naila Parveen (Annals of Human and Social Sciences, 2024)
Pakistan’s Sindh province is home to Karachi. Thus, the project is based on the changes in Karachi’s land cover as seen by satellite imagery. The city contains a significant amount of open space as well as streams and estuaries, while having the highest density of population. All of the things that I have to keep an eye on, such as settlements, vegetation, the road system, agricultural regions, bare soil, coastal areas, barren areas, etc., can be clearly distinguished using satellite imagery from Landsat TM 30m in the years 2000, 2003, and 2014. Techniques from GIS and remote sensing are applied. Unsupervised classification has been carried out in all images. The work’s outcome demonstrates a sharp increase in Karachi’s built-up area between all of the aforementioned years, as well as a shift in the city’s open spaces and decreased vegetation.